2001
DOI: 10.1603/0022-0493-94.4.898
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness of 79 Compounds and Mixtures to Wild <I>Ceratitis capitata</I> (Diptera: Tephritidae) in Field Trials

Abstract: Seventy-nine volatile compounds chosen from those emitted by Mediterranean fruit fly males, fruits and food baits, were tested for their attractiveness to females of Ceratitis capitata (Wiedemann) in field trials with a wild population. To correct for density fluctuations, the results were presented as a percentage of males caught in the same type of traps baited with trimedlure, a known male attractant. The mixtures of corn steep liquor with ammonia compounds and amines were the most effective attractants for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 31 publications
(47 reference statements)
0
7
1
Order By: Relevance
“…Field trials further revealed that total male extracts as well as synthetic blends of major components were highly attractive to wild females, the majority of which were virgin. Thus, in contrast to other studies (Heath et al 1991;Casaña-Giner et al 2001), the total extracts and blends tested by Mavraganis et al (2008) appear to be highly attractive to female medflies and clearly merit additional field testing.…”
Section: Ceratitis Pheromonescontrasting
confidence: 62%
See 2 more Smart Citations
“…Field trials further revealed that total male extracts as well as synthetic blends of major components were highly attractive to wild females, the majority of which were virgin. Thus, in contrast to other studies (Heath et al 1991;Casaña-Giner et al 2001), the total extracts and blends tested by Mavraganis et al (2008) appear to be highly attractive to female medflies and clearly merit additional field testing.…”
Section: Ceratitis Pheromonescontrasting
confidence: 62%
“…Although females showed greatest attraction to live males, the five component blend was more attractive than the individual compounds and appeared to elicit a much greater female response than the 3-component blend used by Landolt et al (1992a). While the above studies reveal the attractiveness of simple pheromone blends, Casaña-Giner et al (2001) reported very low catch of female medflies in traps baited with a 6-component mixture and questioned the long-range effectiveness of male pheromone-baited traps.…”
Section: Ceratitis Pheromonesmentioning
confidence: 99%
See 1 more Smart Citation
“…NuLure), but less effective than Torula yeast . In Spain, corn‐steep liquor mixed with ammonia and amines were the most effective attractants for female C. capitata . In Mexico, commercial proteinaceous baits (Torula yeast and Ceratrap) were tested against grape juice for attraction of Anastrepha fruit flies in citrus .…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In Spain, corn-steep liquor mixed with ammonia and amines were the most effective attractants for female C. capitata. 24 In Mexico, commercial proteinaceous baits (Torula yeast and Ceratrap) were tested against grape juice for attraction of Anastrepha fruit flies in citrus. 25 Low efficacy, male-biased captures, high non-target and beneficial insect captures, and the need for frequent re-baiting were the main drawbacks.…”
Section: Discussionmentioning
confidence: 99%